BENEFITS OF WATCHING MOVIES AND SERIES IN ENGLISH - Kenjaboyeva O`g`iljon To`xtaboy qizi; Ne'matova Madina Baxtiyor qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article examines the educational and linguistic benefits of watching movies and series in English. It argues that films and TV shows serve as a powerful medium for language acquisition, improving listening, pronunciation, and vocabulary while enhancing cultural awareness. By observing authentic speech, learners develop natural fluency and grammatical intuition. Furthermore, watching English-language media increases motivation, promotes autonomous learning, and exposes learners to diverse accents and expressions. The article concludes that integrating movies and series into language education offers a dynamic, enjoyable, and effective approach to mastering English in the modern world.